Integrating Qur’anic Verses through a Pop-Up Book on Earth Structure to Enhance Students’ Science Understanding and Spiritual Development : Penelitian - Uki Adi Prasetiya; Akhmad Dalil Rohman; Tri Unggul Sari Asih; Ely Mufidah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to describe the integration of Islamic values into Natural Science (IPAS) learning, specifically on the topic of the Earth's structure, and to analyze the role of Pop-Up media in realizing this integration at the Elementary School (SD/MI) level. The primary purpose of this integration is to holistically educate students, fostering not only intellectual competence but also spiritual strength, characterized by gratitude, a sense of responsibility as guardians of the Earth (khalifah), and deep contemplation (tadabbur) of Allah's creation. Employing a qualitative approach with a library research method, this study analyzes data from relevant scientific literature using content analysis techniques. The findings reveal that the integration of Islamic values can be achieved by correlating scientific concepts of the Earth's structure with relevant Qur'anic verses. Pop-Up media serves as an effective bridge to concretize abstract concepts through interactive three-dimensional visualizations, simultaneously enhancing students' conceptual understanding of science and strengthening their spiritual values. This study recommends that educators develop Islamic-themed Pop-Up media for other science topics to create holistic, contextual, and character-rich learning experiences.